2014
DOI: 10.1007/s10103-014-1650-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LLLT on endothelial cells culture

Abstract: Growth factors as vascular endothelial growth factor (VEGF), produced by the endothelial cells, take an essential part in pathological and physiological angiogenesis. The possibility of angiogenesis modulation by application of laser radiation may contribute to the improvement of its use in this process. Thus, the aim of the study was to investigate the influence of low-level laser therapy (LLLT) on the proliferation of endothelial cells, secretion of VEGF-A and presence of soluble VEGF receptors (sVEGFR-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…The rationale of its clinical use is based on its ability to accelerate the wound‐healing process by promoting vascularization, 15 production of collagen, 16 fibroblasts, 17 and epithelial tissue 18 . Furthermore, low‐intensity laser irradiation also promotes analgesia, reduction of edema, and anti‐inflammatory effects 19–22 …”
mentioning
confidence: 99%
“…The rationale of its clinical use is based on its ability to accelerate the wound‐healing process by promoting vascularization, 15 production of collagen, 16 fibroblasts, 17 and epithelial tissue 18 . Furthermore, low‐intensity laser irradiation also promotes analgesia, reduction of edema, and anti‐inflammatory effects 19–22 …”
mentioning
confidence: 99%
“…Schindl et al [36] evaluated in vitro the effects of 670-nm LLL irradiation with different dosimetries, showing that energy densities of 2, 4, and 8 J/cm 2 stimulated endothelial cell proliferation. Similarly, Góralczyk et al [18] found that 635-nm LLL irradiations with similar energy densities stimulated cellular proliferation and positively modulated growth factors and receptors involved in the mechanism of vascular neoformation. Based on this information, the wavelength (660 nm) and energy density (2.5 J/cm 2 ) of the red laser employed in our study probably favored the repair of the pulp tissue.…”
Section: Discussionmentioning
confidence: 87%
“…Inflammation is part of the repair process that involves the migration of leukocytes, cell differentiation, and proliferation [18][19][20]. Some studies evaluated the expression of markers related to the process of tooth tissue formation after pulp treatment with different materials in animals [21,22] and human teeth [1].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in static and dynamic planter pressure after 850 nm He Ne laser therapy treatment can be explained as laser improve peripheral neural function of both sensory and motor nerve with significant decrease in the pain level. Previous researchers found that athermic laser therapy induced a significant reduction of pain and increase in skin microcirculation in diabetic microangiopathy patients [18,36]. All of these effects can be reflect clinically and functionally to readjust distribution of planter pressure during standing through decrease static planter pressure and during walking by decrease dynamic planter pressure.…”
Section: Discussionmentioning
confidence: 92%